2003
DOI: 10.1098/rspb.2002.2217
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off between immunocompetence and growth in magpies: an experimental study

Abstract: A trade-off between immunity and growth has repeatedly been suggested, mainly based on laboratory and poultry science, but also from experiments where parasitism intensity was manipulated in field bird populations. However, as resource allocation to different activities (or organs) during growth is difficult to manipulate, this trade-off has only been experimentally tested by studying the effects of non-pathogenic antigens. By providing some nestling magpies (Pica pica) with methionine, a sulphur amino acid th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
219
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 226 publications
(234 citation statements)
references
References 43 publications
11
219
1
3
Order By: Relevance
“…An exaggerated allocation to T-cell-mediated immunocompetence therefore trades-off with growth and has clear (survival) costs in blue tits nestlings. In the only other study to date that has directly manipulated allocation to immunocompetence in the wild, Soler et al (2003) found that growth in magpies was initially reduced while T-cell-mediated immunocompetence was increased. However, neither fledging condition nor survival to fledging was affected (Soler et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An exaggerated allocation to T-cell-mediated immunocompetence therefore trades-off with growth and has clear (survival) costs in blue tits nestlings. In the only other study to date that has directly manipulated allocation to immunocompetence in the wild, Soler et al (2003) found that growth in magpies was initially reduced while T-cell-mediated immunocompetence was increased. However, neither fledging condition nor survival to fledging was affected (Soler et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Nestlings were ordered by their weight and the treatment of the heaviest chick was decided at random. The treatment of all other chicks then alternated down the size hierarchy (see also Soler et al 2003). The individual markings on the feet of the nestlings were remade at every consecutive visit until chicks could be ringed (at around days 8-10).…”
Section: (B) Experimental Protocolmentioning
confidence: 99%
See 3 more Smart Citations